2021
DOI: 10.1186/s40644-021-00414-6
|View full text |Cite
|
Sign up to set email alerts
|

MRI-based radiomics models to assess prostate cancer, extracapsular extension and positive surgical margins

Abstract: Purpose To investigate the performance of magnetic resonance imaging (MRI)-based radiomics models for benign and malignant prostate lesion discrimination and extracapsular extension (ECE) and positive surgical margins (PSM) prediction. Methods and materials In total, 459 patients who underwent multiparametric MRI (mpMRI) before prostate biopsy were included. Radiomic features were extracted from both T2-weighted imaging (T2WI) and the apparent diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 39 publications
0
39
2
Order By: Relevance
“…Bai et al (39) reported their radiomic model could predict the presence of ECE preoperatively, but the AUC value of their integrated model was only 0.71, much lower than ours (AUC = 0.85). He et al (40) used MP-MRI radiomics to predict ECE (AUC = 0.728, also lower than ours) and SM (AUC = 0.76, similar to ours), yet they did not comprehensively evaluate the aggressiveness of prostate cancer as ours. Therefore, our comprehensive radiomic models made it possible to predict more critical biological characteristics of prostate cancer and improve the prediction accuracy of some biological characteristics compared with the other published AI models.…”
Section: Discussionmentioning
confidence: 44%
“…Bai et al (39) reported their radiomic model could predict the presence of ECE preoperatively, but the AUC value of their integrated model was only 0.71, much lower than ours (AUC = 0.85). He et al (40) used MP-MRI radiomics to predict ECE (AUC = 0.728, also lower than ours) and SM (AUC = 0.76, similar to ours), yet they did not comprehensively evaluate the aggressiveness of prostate cancer as ours. Therefore, our comprehensive radiomic models made it possible to predict more critical biological characteristics of prostate cancer and improve the prediction accuracy of some biological characteristics compared with the other published AI models.…”
Section: Discussionmentioning
confidence: 44%
“…The currently existing data are promising, with radiomics outperforming PIRADS v2 in the detection of high-grade versus low-grade PCa, although some limitations remain regarding the standardization of data, and further studies are required to confirm the performance of radiomics compared to conventional radiological analysis [ 92 ]. Moreover, radiomics models are useful in the detection of prostate extracapsular extension (ECE), and allows predictive models to be build for the pretreatment detection of ECE, focusing on a combined model of clinical, conventional radiology and radiomics [ 93 , 94 , 95 ].…”
Section: Resultsmentioning
confidence: 99%
“…Despite this, there is still room for improvement in mpMRI reporting. Hence, efforts have been made to implement computer-aided diagnosis (CAD) coupled with radiomics and machine learning to predict GS from clinical images, with the aim to bypass interobserver variability, showing promising results [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%